Comparative study of the use of coagulants in biologically treated palm oil mill effluent (POME) - Jami, Mohammed Saedi; Muyibi, Suleyman Aremu; Idris Oseni, Munirat (American-Eurasian Network for Scientific Information (AENSI), 2012)
The production of palm oil results in the generation of huge quantities of polluting wastewater commonly known as Palm Oil Mill Effluent (POME). POME is a thick brownish liquid that contains high amount of total solids, oil and grease, chemical oxidation demand (COD), biochemical oxygen demand (BOD), and if not properly treated, can disrupt the natural ecosystem and pose a serious threat to human health. However, with the stringent regulations on discharge of waste into the environment, there is need to retrofit the existing biological system by adding tertiary treatment in form of coagulation to remove contaminants in order to meet the current discharge regulations. This paper compares the use of coagulants ferric chloride and aluminium sulphate to reduce turbidity that is associated with the effluent. Series of batch coagulation and flocculation processes with ferric chloride and aluminum sulphate under different conditions, i.e. dosage and pH were conducted in order to determine their optimum conditions. Polyacrylamide was used as coagulant aid and its optimum dose was also determined. The result of the coagulation process showed that ferric chloride gave a better reduction of turbidity at dosage of 100mg/L, pH of 8 and with polyacrylamide (coagulant aid) dose of 100mg/L than alum.